The Effect of Puzzle-Assisted Team Games Tournament on Junior High School Students’ Critical Thinking Skills and Cognitive Science Learning Outcomes - Muhammad Fakhri Risqullah; I Wayan Karmana; Septiana Dwi Utami (Lombok Institute, 2026)
This study analyzed the effect of puzzle-assisted Team Games Tournament (TGT) on students’ critical-thinking skills and cognitive learning outcomes in science. A quasi-experimental nonequivalent control group design was employed. The population comprised 102 seventh-grade students at SMPN 2 Pringgarata across four classes. Purposive sampling was based on comparable academic characteristics and previous-semester achievement, resulting in Class VII A as the experimental group (n = 30) and Class VII B as the control group (n = 33). The intervention was implemented in two meetings between October 1 and 14, 2019. The experimental group participated in TGT integrating a colored two-dimensional picture puzzle during team study, games, and tournament activities, whereas the control group received conventional instruction through teacher explanation, question-and-answer activities, and assignments. Data were collected using an instructional implementation observation sheet, five essay items for critical-thinking skills, and 25 multiple-choice items for cognitive learning outcomes. The experimental group’s mean critical-thinking score increased from 60 to 90, whereas the control group’s mean increased from 55 to 80. The experimental group’s mean cognitive score increased from 58 to 76, whereas the control group’s mean remained at 54. Independent-samples t-tests on posttest scores indicated significant differences in critical-thinking skills, t(61) = 4.677, p < .001, g = 1.17, and cognitive learning outcomes, t(61) = 6.502, p < .001, g = 1.62. The normalized gain for critical thinking was 0.75 in the experimental group and 0.56 in the control group; the corresponding values for cognitive learning outcomes were 0.43 and 0.00. Students participating in puzzle-assisted TGT achieved higher outcomes than those receiving conventional instruction. The findings should be interpreted cautiously because classes were not randomly assigned and the study was conducted at a single school.